Assessing household poverty and wellbeing: a manual with examples from Kutai Barat, Indonesia - Cahyat, A.; Gonner, C.; Haug, M. (Center for International Forestry Research, 2007)
The manual reflects the results of a 3-year participatory learning process that comprised many meetings, workshops, village case studies, a baseline survey of 20 poor villages, two monitoring trials in another 20 villages, and a full monitoring survey of all 223 villages in Kutai Barat. The principal purpose of this manual is to provide technical guidelines and background information to poverty assessors at district, subdistrict and village level in Kutai Barat. Therefore, the manual is structured in modules according to the tasks of the assessors. It describes the poverty monitoring system step by step, from the development of local poverty indicators to the final analysis and application of monitoring data.